МАГНІТОЕЛЕКТРИЧНИЙ ПЕРЕТВОРЮВАЧ ЕНЕРГІЇ МОРСЬКИХ ХВИЛЬ - Ращепкін, А.П.; Кондратенко, І.П.; Карлов, О.М.; Крищук, Р.С. (Інститут електродинаміки НАН України, Київ, 2021)
To convert the energy of sea waves, the use of cylindrical (with a radial magnetic flux) three-phase magnetoelectric generators with a permanent magnet rotor using a mechanical gearbox to increase the rotor speed is considered. Given the real rotor motion, a mathematical model has been developed to calculate the distribution of magnetic fields in the gap of the generator, and functional dependences of the flux linkage of the winding and the electromagnetic moment of the generator on its design and the parameters of permanent magnets have been obtained. For the adopted design, the electromagnetic moment, the distribution of phase currents in the windings, the power and voltage of the generator are determined. A comparison is made of the energy performance of generators with a traditional float drive and using a ratchet to ensure one-sided rotation of the rotor. The expediency of using a ratchet generator to convert the energy of sea waves is considered. References 6, figures 7.